2011
DOI: 10.1111/j.1752-699x.2011.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and complications following medical thoracoscopy

Abstract: Introduction: Thoracoscopy is an invasive procedure that may be performed by physicians for the investigation of exudative pleural effusion using local anaesthesia, conscious sedation and a rigid thoracoscope. Objectives: We sought to evaluate the safety and outcome of thoracoscopy in Portsmouth Hospitals, UK, a dockyard city with high previous asbestos usage. Methods: Retrospective casenote, radiology and laboratory result analysis of patients undergoing thoracoscopy in our institution over a 12-month period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…Our study showed a large number of patients, with active malignancy who were diagnosed with non‐malignant pleural effusions by pleuroscopy (58%). Surprisingly, this is comparable to the prevalence of malignancy in other studies of pleuroscopy where the patient population was more general . Review of clinical and radiographical data was sufficient to reach a diagnosis in 70% of patients, the majority of which were related to cancer therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed a large number of patients, with active malignancy who were diagnosed with non‐malignant pleural effusions by pleuroscopy (58%). Surprisingly, this is comparable to the prevalence of malignancy in other studies of pleuroscopy where the patient population was more general . Review of clinical and radiographical data was sufficient to reach a diagnosis in 70% of patients, the majority of which were related to cancer therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Serious complications following thoracoscopy are rare (Brims et al [21]). The procedure is generally considered to be safe and well-tolerated, especially with semi-rigid instruments with no reported mortality to date (Lee and Colt [22]; Mohan et al [23]).…”
Section: Discussionmentioning
confidence: 98%
“…Although thoracoscopy is able to determine a clear diagnosis and make pathological classifications of these lesions, it requires specialized technology and has high risk, even mortality [4]. This is less likely to be used as the sole diagnostic instrument.…”
Section: Discussionmentioning
confidence: 99%
“…However, endoscopic information often fails to successfully detect peripheral airways smaller than 2 mm in diameter [3]. In addition, due to challenging technology and the potential for severe complications, thoracoscopy is not commonly used as a diagnostic tool alone [4], [5].…”
Section: Introductionmentioning
confidence: 99%